E-marketplace Optimization as Marketing Tool for Makmur Jaya Farmer Group Products in Meddelan Village to Enhance Farmers' Welfare: Optimalisasi E-marketplace Sebagai Sarana Pemasaran Produk Kelompok Tani Makmur Jaya Di Desa Meddelan Sebagai Upaya Peningkatan Kesejahteraan Petani - Faikul Umam; Firmansyah Adiputra; Achmad Zain Nur (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
Meddelan village in Lenteng sub-district, Sumenep district, is an agricultural area where the majority of residents work as farmers. Despite the large production potential, the farmers in this village, especially the Makmur Jaya Farmers Group, face various problems in increasing the selling value of their agricultural products. One of the main challenges is limited access to markets that still rely heavily on conventional methods such as middlemen, who often offer prices below market value. In addition, the low level of digital skills among farmers is an obstacle in utilizing e-marketplace technology that can expand market reach and provide more competitive selling prices. This condition is exacerbated by the lack of a structured marketing strategy and supporting infrastructure such as limited internet access. To overcome this problem, a community service program focused on optimizing the use of e-marketplace as a means of marketing agricultural products was implemented. This program includes intensive training for farmers in the use of e-marketplace platforms, improving digital skills, and forming effective digital marketing strategies. In addition, Merdeka Belajar Kampus Merdeka (MBKM) students are also involved in this activity to assist farmers in every stage of implementation, from training to evaluation. This activity is expected to become a technology-based farmer empowerment model that can be applied in other areas with similar situations.